(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Internet has emerged as a necessary part of our life. Adolescent have become entirely dependent on the internet to search for information, social website, recreation, online purchasing and online gaming. Educational institutions around the world are making use of the internet to upgrade teaching and studying indoors or outside the classroom using the internet. As India is overrunning towards digitalization and along with showing technological advancement and usefulness. It has also presented some deplorable outcome for the adolescents. The present research work is to find out the impact of technology advancement focusing the internet usage, with reference to positive and negative effect. The researcher has attempted to recognize the several factors having influence on youth’s internet addiction level and also analysis the effects. To overcome all these negative effects of internet and technology, the parents needs to monitor their children on regular basis.